Best practices for selecting samples, analyzing data, and publishing results in isotope archaeology. (20th March 2023) - Vaiglova, Petra; Lazar, Nicole A.; Stroud, Elizabeth A.; Loftus, Emma; Makarewicz, Cheryl A.
Abstract: Isotopic analysis has become one of the most popular arenas of archaeological science, in part due to its versatility to uncover intriguing insights from a range of organic and inorganic archaeological materials. However, alongside an increase in popularity, the field has seen the rise of dissemination of publications that do not pass quality control, do not apply robust interpretative frameworks, or do not report data in ways that would make them amenable to critical evaluation or inclusion in large meta-analyses. This paper represents an effort to clarify some of the most pressing weaknesses and misconceptions in 'traditional' applications of isotopic techniques in archaeology: measurement of stable carbon, nitrogen, and oxygen isotope values of organic and inorganic materials (bulk bone collagen, bulk tooth dentine, seeds; bulk and incremental tooth enamel, molluscan shells), and strontium isotope ratio analysis of tooth enamel and cremated bone. The discussion centers on three key aspects of research: (1) Selecting samples, with advice on building comparative baselines (or more appropriately 'base intervals ') and words of caution on interpreting stable carbon isotope values measured during AMS radiocarbon dating. (2) Handling data, including tips on exploratory data analysis, graphical visualization, and statistical assessment of differences between groups; with particular reference to the Statement on p -values published by the American Statistical Association. (3) Reporting results, with advice on using correct terminology and decimal points, calculating measurement precision and accuracy, and communicating results using effective scientific language. The advice provided in this paper does not cover all aspects of project design and dissemination but will hopefully provide clarification within the above key areas and inspire further discussion of effective and impactful applications of isotopic techniques in archaeology.